1989
DOI: 10.1542/peds.83.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Replacement in Preschool-Aged Hyperactive Boys

Abstract: A 10-week study was conducted in which all food was provided for the families of 24 hyperactive preschool-aged boys whose parents reported the existence of sleep problems or physical signs and symptoms. A within-subject crossover design was used, and the study was divided into three periods: a baseline period of 3 weeks, a placebo-control period of 3 weeks, and an experimental diet period of 4 weeks. The experimental diet was broader than those studied previously in that it eliminated not only artificial color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In three studies comparing hyperactive children with age-matched controls, we found no evidence of differences in sleep latency or quantity, but clear evidence that hyperactives experience night wakings more frequently (Kaplan, McNicol, Conte, & Moghadam, 1987b). In related research of hyperactive preschool-aged boys participating in a dietary intervention study, however, we could detect no relationship between serum tryptophan levels and sleep variables (Kaplan et al, in press b).…”
Section: Hyperactivity and Arousalmentioning
confidence: 60%
See 2 more Smart Citations
“…In three studies comparing hyperactive children with age-matched controls, we found no evidence of differences in sleep latency or quantity, but clear evidence that hyperactives experience night wakings more frequently (Kaplan, McNicol, Conte, & Moghadam, 1987b). In related research of hyperactive preschool-aged boys participating in a dietary intervention study, however, we could detect no relationship between serum tryptophan levels and sleep variables (Kaplan et al, in press b).…”
Section: Hyperactivity and Arousalmentioning
confidence: 60%
“…Unlike the other two replacement studies, our elimination diet excluded a broader range of foods than those targetted by Feingold, although fewer than those found by Egger et al (1985) to be possible problems. The results of our study were that roughly half of our 24 subjects exhibited approximately a 50% improvement in behaviour, also in home-based measures, while on the experimental diet (Kaplan et al, in press b).…”
Section: Hyperactivity and Arousalmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, the parental investment needed to apply a strenuous dietary intervention could underlie the relatively large effects. However, parental investment in various trials of the few-foods diet has been found to be marginal [65,[68][69][74][75] .…”
Section: Meta-analysis Of Few-foods Diet Trialsmentioning
confidence: 99%
“…We identified two studies (Bateman et al, 2004; Kaplan, McNicol, Conte, & Moghadam, 1989) focused on diet restrictions (i.e., additive-free or few-food diets) with a focus on preschool children with or at high-risk for ADHD. In a within-subject, placebo-controlled, double-blind, crossover study, Kaplan and colleagues (1989) observed significant effects of dietary restrictions on parent report of ADHD behaviors, on parent-identified idiosyncratic target behaviors, and on sleep outcomes; however, no significant effects were observed on behaviors as reported by daycare staff or on parent report of physical symptoms. The authors note that 42% of participants were considered nonresponders to treatment.…”
Section: Literature Reviewmentioning
confidence: 99%